Trends in mortality, disability-adjusted life years, and years of healthy life lost due to self-harming in Brazilian states from 1990 to 2019 - Milena Sabino Fonseca; Gustavo Gusmão dos Santos; Patricia Colombo de Souza; Lúcia Helena de Azevedo; Jane de Eston Armond; Lucas Melo Neves (Revista de Saúde Pública)
ABSTRACT OBJECTIVES To compare rates, disability-adjusted life years (DALYs), and years of healthy life lost due to disability (YLDs) associated with deaths due to self-harm in Brazil. METHODS This epidemiological study utilized secondary data obtained from the Global Burden of Disease Study. Analytical examinations were conducted to provide detailed descriptions of national and subnational rates. RESULTS We identified mortality rates, DALYs, and YLDs resulting from deaths due to self-harm - national data from 26 states and the Federal District - between 1990 and 2019. The national rates in 1990 and 2019 were the same for mortality = 6.2 deaths per 100.000 inhabitants, reduced for DALYs = 312-289 DALYs, and the same for YLDs = 1.6 YLDs. Four united federations had higher mortality rates, DALYs, and YLDs caused by self-harm compared to national rates throughout the analyzed period (between 1990 and 2019) – Goiás (mortality = 11-67%, DALYs = 13-73%, and YLDs = 4-45%), Mato Grosso do Sul (mortality = 23-42%, DALYs = 28-46%, and YLDs = 13-64%), Minas Gerais (mortality = 5-25%, DALYs = 7-25%, and YLDs = 19-35%), and Rio Grande do Sul (mortality = 73-98%, DALYs = 55-84 %, and YLDs = 52-70%). CONCLUSION Although national mortality rates and YLD caused by self-harm have been maintained, there has been a decrease in the incidence of DALYs. However, certain states in Brazil have rates higher than the national average, indicating the need for multiple strategies to be implemented to reduce mortality rates, DALYs, and YLDs resulting from self-harm in these specific states.